PUBLIC INVESTMENT POLICY AS A DRIVER OF CHANGES IN THE ECOSYSTEM SERVICES DELIVERY BY AN URBAN GREEN INFRASTRUCTURE - Abramowicz, Dawid; Stępniewska, Małgorzata (Quaestiones Geographicae, 2020)
The presented study considers the impact of public expenditure related to land development on the potential of an urban green infrastructure to provide ecosystem services (ES). The study site (Szachty) is located in Poznań, the fifth largest city in Poland. In the article, we recognised the type of expenditure (permanent infrastructure and ongoing maintenance), the costs and the influence on ES (stimulating, weakening or no relevant). The study shows that the financial policy concerning the study area is focused on creating an infrastructure that enhances cultural ecosystem services (CES). However, the creation of recreational facilities weakens the potential of the area for supplying regulating services concerning maintaining nursery populations and habitats. The results highlight the need for scientific support for policymakers in understanding the synergies and trade-offs between ES, resulting from financial decisions. This is particularly important in the decision-making process in the areas of high natural value, in which full, long-term effects of the decisions may be barely visible and incomprehensible for the society. Showing the impact of financial decisions on the structure and level of ES may provide arguments supporting a more complex and high-quality social dialogue, including balancing the interests of various stakeholders.